“Canning the kaiser” in words and images - Hazemali, David (ELOPE (Ljubljana), 2023)
The article examines how the US government used poetry and posters as instruments of propaganda during World War I to mobilize the nation and resources for their war effort and to denigrate the enemy, especially the German Emperor, Kaiser Wilhelm II. Two case studies are presented: the poem "Canning the Kaiser” by the American writer Upton Sinclair and the poster “Can Vegetables, Fruit and the Kaiser Too” by the Belgian-American artist Jozef Paul Verrees. The article explores the historical context of Sinclair’s poem as well as the use of humour, irony, and visual metaphors in both pieces of art to persuade the American public to conserve food, support the troops, and thus help defeat the Kaiser. A particular interest of this study lies in the idiomatic meaning of the phrase “Canning the Kaiser”, which is not only an intriguing linguistic issue but had a considerable impact on the development of the campaign.
Keywords: poetry; poezija; posters; propaganda; propagandni plakati; prva svetovna vojna